2023
DOI: 10.1101/2023.03.06.531282
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cytotoxic CD4+T cells eliminate senescent cells by targeting cytomegalovirus antigen

Abstract: Senescent cell accumulation has been implicated in the pathogenesis of aging-associated diseases including cancer. The mechanism that prevents the accumulation of senescent cells in aging human organs is unclear. Here, we demonstrate that a virus-immune axis controls the senescent fibroblast accumulation in the human skin. Senescent fibroblasts increased in old compared with young skin. However, they did not increase with advancing age in the elderly. Increased CXCL9 and cytotoxic CD4+ T cell (CD4 CTL) recruit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Although NKG2D-CAR T cells have shown a favorable safety profile in cancer clinical trials, it is essential to thoroughly investigate their safety and potential toxicities in older individuals through clinical studies. NKG2DLs are highly expressed in senescent cells from aged individuals ( 50 ), and our studies demonstrated that NKG2D-CAR T cells do not exhibit overt toxicity in aged mice and nonhuman primates. These findings suggest that the adoptive transfer of engineered T cells armed with NKG2D-CAR, specifically targeting naturally occurring senescent cells expressing NKG2DLs, could have an impact on the field of geriatric medicine.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Although NKG2D-CAR T cells have shown a favorable safety profile in cancer clinical trials, it is essential to thoroughly investigate their safety and potential toxicities in older individuals through clinical studies. NKG2DLs are highly expressed in senescent cells from aged individuals ( 50 ), and our studies demonstrated that NKG2D-CAR T cells do not exhibit overt toxicity in aged mice and nonhuman primates. These findings suggest that the adoptive transfer of engineered T cells armed with NKG2D-CAR, specifically targeting naturally occurring senescent cells expressing NKG2DLs, could have an impact on the field of geriatric medicine.…”
Section: Discussionmentioning
confidence: 52%
“…Although it was previously reported that senescent cells escape from endogenous NKG2D-mediated NK cell immunosurveillance during aging ( 18 ), our results demonstrate that senescent cells expressing NKG2DLs in vivo can be selectively and effectively eliminated by the adoptive transfer T cells armed with NKG2D-CARs. Recent studies have found higher expression of NKG2DLs (ULBP2 and MICA) in senescent fibroblasts present in the skin of older individuals in comparison with younger individuals ( 50 ). Our studies indicate that senescent cells expressing NKG2DLs in aged humans could potentially be targeted using NKG2D-CAR T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Dermal fibroblasts were isolated from collected skin samples in wound healing assay, according to previous reports ( 9 , 75 ). After removing subcutaneous fat tissues with a scalpel, skin tissues were incubated in Elastase (0.12 mg/ml; STEMCELL, #07453) in DMEM at 37°C for 25 min to separate dermal and epidermal.…”
Section: Methodsmentioning
confidence: 99%
“…Senescent cells (SnCs) accumulate in tissues with aging, contributing to the development of age-related pathologies and declines, mainly via senescence-associated secretory phenotype (SASP) ( 6 8 ). Through secreting proinflammatory and tissue-remodeling factors, SnCs communicate with surroundings and fuel a chronic inflammatory microenvironment in the body, which seriously impedes the damaged tissue repair ( 9 , 10 ). Moreover, SnCs are characterized with DNA damage, cell cycle arrest, metabolic changes, mitochondria dysfunctions, and reduced autophagy, underlying the impaired capacity for wound repair in aging tissues ( 8 , 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The escape‐from‐senescence phenomenon could also be a mechanism contributing to this outcome (see the next section). Ever since GL13 discovery, the spectrum of pathological entities has been expanded to include benign, preneoplastic, and neoplastic lesions, while senescent cells have also been recognised in various experimental and ageing contexts (Table 2) [37,106,107,110–137]. In particular, in clinical settings, skin pathologies (nevi, seborrheic, and actinic keratoses), lung, pancreatic, urothelial and laryngeal precancerous lesions, various types of carcinomas following treatment, sarcomas, haematological malignancies (Langerhans histiocytosis), and a variety of tissues from aged organs were included (Table 2).…”
Section: Detecting Senescence Escape: a Challenging Taskmentioning
confidence: 99%